Development of students' understanding of the meaning of humanitarian subjects and their interest in reading - Rajeckas, V. (Psichologija, 1977)
The article shows how in the years 1960-1976 students understood the significance of the humanities in the aspects in which they valued them most. Their views on the literature reveal data on the number of books and authors read by boys and girls in grades 9-11. The books read at home are compared to the works of fiction examined during the lessons. The article analyzes what newspapers and magazines students read and what issues of periodicals they are interested in.
Keywords: humanitariniai dalykai; reikšmės suvokimas; skaitymo interesai